Sur les points singuliers des fonctions représentées par les séries de Taylor—Dirichlet - Konov, V. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. И. Конов. Об особых точках функций, представимых рядами Тейлора—Дирихле V. Konovas. Teiloro—Dirichle eilutės pavienių taškų klausimu